The stress of subordinance: Socially mediated differences in acid-base regulation in rainbow trout (Oncorhynchus mykiss) - Mussa, Beidan (University of Ottawa (Canada), 2009)
Rainbow trout (Oncorhynchus mykiss) held in pairs engage in agonistic interactions resulting in one fish becoming dominant over the other, subordinate fish. Subordinate social status constitutes a chronic stress with subordinate fish exhibiting a prolonged elevation of circulating cortisol levels that in turn leads to reduced growth rates, altered metabolic function and compromised immune responses. The chronic stress experienced by subordinate fish also impacts ionoregulatory ability. Owing to the tight coupling between Na+ and Cl- uptake and, respectively, H + and HCO3- excretion at the gill, such ionoregulatory changes may affect acid-base regulation. Thus, the present study investigated the impact of social status on acid-base regulation of respiratory acidosis in rainbow trout. Responses of subordinate, dominant and control trout to 24 h of hypercapnia were compared. Social status appeared to impact net acid excretion (JnetH +) as subordinate individuals were unable to increase net acid flux in response to hypercapnia. However, despite this impaired response, blood acid-base status was found to be unaffected by social status before or during hypercapnic exposure, indicating that subordinate fish were as effective as dominant or control trout in achieving compensation for the acid-base disturbance. Compensation in all groups involved decreasing Cl- uptake in response to hypercapnia, thereby reducing HCO3- loss. Differences in branchial and renal Na+, K+-ATPase and H+-ATPase activities were documented between subordinate and dominant/control trout. Subordinate individuals exhibited elevated circulating cortisol concentrations prior to hypercapnia and failed to exhibit further increases in circulating cortisol levels in response to the acute stress of hypercapnia. Taken as a whole, the findings of this study suggest that subordinate fish are able to regulate body fluid pH during a respiratory acidosis, but this regulation may come at a greater cost than is the case in dominant or control fish.
Keywords: Biology, Animal Physiology.